Stability evaluation of candidate reference genes for RT-qPCR normalization in Lasioderma serricorne (F.). (December 2021) - Zhang, Yue; Yang, Jia-peng; Dai, Ren-huai; Yan, Yi; Yang, Wen-jia; Hu, Da-ming
Abstract: Lasioderma serricorne (Fabricius) is an important insect pest of stored products worldwide. The real-time quantitative polymerase chain reaction (RT-qPCR) is a reliable technique commonly used to analyze gene expression across various biological processes. For accurate gene expression analyses using RT-qPCR, selection of stable reference genes to normalize RT-qPCR data is a prerequisite. However, the lack of studies on validation of reference genes in L. serricorne limits application of RT-qPCR in L. serricorne . In this study, the expression stability of eleven candidate reference genes ( Actin, ARF1, β-Tubulin, EF1α, SYN6, TBP1, RPL3, RPL12, RPL13a, RPL32, 18S rRNA using five algorithms (geNorm, NormFinder, BestKeeper, ΔCt and RefFinder) in L. serricorne under different experimental and biotic conditions was assessed. The results showed that the best combinations of reference genes that could be used as internal controls in L. serricorne were 18S rRNA and RPL13a for different development stages; 18S rRNA and RPL3 for different larval tissues; RPL3 and RPL13a for different temperatures; RPL32, RPL12 and Actin for starvation. These results provided for the first time a comprehensive list of stable reference genes for the normalization of RT-qPCR analyses in L. serricorne and will benefit the in-depth molecular biology research in the future. Highlights: The choice of reference gene will still depend on the experiment. 18S rRNA and RPL13a are the optimal candidate reference gene combination for developmental stages. 18S rRNA and RPL3 are the optimal candidate reference gene combination for larvae tissues. RPL3 and RPL13a are the optimal candidate reference gene combination for temperature stress. RPL32, RPL12 and Actin are the optimal candidate reference gene combination for starvation stress.